Prediction of hepatic fibrosis using the aspartate transaminase-to-platelet ratio index in children and adolescents with metabolic dysfunction-associated steatotic liver disease - Hye Young Jin; Eu Seon Noh; Hwalrim Jeong; II Tae Hwang (BMC, 2024)
Abstract Background Aspartate transaminase-to-platelet ratio index (APRI) is an easy and useful predictor of hepatic fibrosis in patients with chronic hepatic disease, and it significantly correlates with the degree of hepatic fibrosis in adult patients with metabolic dysfunction-associated steatotic liver disease (MASLD). This study aimed to evaluate the use of APRI in assessing the severity of MASLD in children and adolescents. Methods Medical records of 115 patients (males: 78; females: 37) with MASLD were retrospectively reviewed. The correlations between the APRI and clinical parameters that indicate the severity of MASLD were analyzed. Their ages ranged between 7.3 and 18.8 years old. Patients with hepatitis B or C infections were excluded from the study. The APRI score was calculated, and transient elastography for liver stiffness measurement (LSM) was performed for all the patients. Results The mean APRI score was 0.46 ± 0.26, ranging between 0.16 and 1.57. The LSM values ranged between 2.94 and 7.72 kPa. Body mass index-standard deviation score, transaminase levels, and HbA1c levels were higher in a group with abnormal LSM when divided into two groups according to LSM. The APRI score was greater in the group with abnormal LSM (0.40 ± 0.17 vs. 0.64 ± 0.40, P < 0.001). The APRI score was associated with LSM (r = 0.354, P < 0.001). Area under the curve of APRI for predicting abnormal LSM was 0.650 (95% confidence interval, 0.517-0.784) with a cutoff value of 0.74. Conclusions APRI score showed weak correlation with LSM. Further study encompassing various severity of hepatic fibrosis is needed for identifying better and sensitive non-invasive indicators in pediatric MASLD.